The Relationship Between Husband’s Support and Coping with the Occurrence of Baby Blues Syndrome in Postpartum Mothers - Rohmah, Yulia; Fitrianur, Widya Lita; Zuhroh, Diah Fauzia; Sari, Diah Jerita Eka (Ahmar Metastasis Health Journal, 2024)
"Baby blues syndrome" refers to the symptoms of postpartum depression experienced by new mothers. The severity of postpartum depression is often exacerbated by the absence of a loving and supportive partner. The purpose of this study was to determine The Relationship between Husband Support and Coping with the Occurrence of Baby Blues Syndrome in Postpartum Mothers in Pangkahwetan Village, Ujung Pangkah Sub-district. The research method used was quantitative research with a cross-sectional approach.  From a total population of 35 people, 33 participants were randomly selected using basic random sampling procedures. Statistical analysis was conducted using the Chi-Square test. The results of the study found a significant relationship between the coping ability of postpartum mothers and the frequency of baby blues, as well as the support provided by the husband. The Chi-Square test showed a significant association with a threshold of 0.007 < 0.05 for husband support. The p-value for coping ability was 0.033, which was above the significance level of 0.05, indicating a less strong correlation in this area. In conclusion, this study highlighted the important role of husband support in reducing postpartum depressive symptoms. However, the coping abilities of postpartum women showed a weaker correlation with the frequency of baby blues. Future studies should consider a larger sample size and include qualitative methods to gain deeper insights into the emotional and psychological experiences of new mothers. Baby blues syndrome” describes the postpartum depression symptoms experienced by mothers. Postpartum depression is getting worse when there is no loving and supportive partner. The researchers in this cross-sectional quantitative study aimed to learn more about the experiences of new mothers facing sadness after giving birth in Pangkahwetan Village, Ujung Pangkah Sub-district. There were 35 people became the population of this research, and 33 people were selected randomly using basic random sampling procedures for this study. Statistical analysis used the Chi-Square test. According to this research, women’s coping abilities after giving birth and the frequency of baby blues were correlated, as was the presence of the husband’s support. The Chi-Square test measured the husband’s acceptance, with a significance threshold of 0.007 < 0.05. The coping p-value of 0.033 was greater than the significance level of 0.05.